Monitoring change in cycling with the Danish bike- traffic index. - Moltved, Niels E. W.; Clausen, Flemming; Jagielska, Zofia; Hansen, Christian Overgård; Nielsen, Thomas A. Sick (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
The Danish Road Directorate has long experience in planning for cycling and the use of bicycle data and indexes. A national cycling index, a bike-traffic-index, was established in 1985, based on bike-flows continuously counted in locations all over the country. The number of counting stations included in the index has been increased over time to improve reliability and allow support for the development and assessment of policies aiming to maintain and further increase cycling. The index is partly fed by the Road Directorate and partly by the municipalities. With its current 61 counting stations in operation, the bike- traffic-index is still ‘thin’ compared to the equivalent car-traffic index, but it does provide consistent evidence on changes in cycling on Danish roads. The paper compares the bike-traffic-index with travel- survey data as indicators of changes in cycling, it presents the methodology and accuracy of the bike-traffic- index, and finally, it discusses its desirable improvements to increase accuracy and detect changes in cycling beyond the fluctuations in weather conditions that are generally important to cycling but also beyond policy reach.